The Influencing Factors Of Tax Management in Go Public Companies on The Indonesia Stock Exchange - Astrinur Rahmawati; Ati Sumiati; Sri Zulaihati (LPPM Universitas Negeri Jakarta, 2020)
This research intends to know an affection between profitability, capital intensity, firm size and leverage on tax management in agricultural, mining and property sector companies that have been listed on the Indonesia Stock Exchange in 2018 and focused on tax avoidance as one of strategies for tax management. The research method used is quantitative method. The type of data research are secondary data obtained using documentation techniques through the company’s financial statements with 87 samples. The data analysis technique using the requirements analysis test, classic assumption test, multiple regression test, and hypothesis test. The partial hypothesis test results show that profitability has no significant effect on tax management; capital intensity has a positive and significant effect on tax management; company size has no significant effect on tax management; and leverage has no significant effect on tax management. Meanwhile, the results of the hypothesis test simultaneously show that profitability, capital intensity, company size, and leverage influence tax management simultaneously.